2012
DOI: 10.1186/1472-6882-12-128
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content, antioxidant effect and cytotoxic activity of Leea indica leaves

Abstract: BackgroundThe leaves of Leea indica (Vitaceae), commonly known as ‘Huo Tong Shu’ in Malaysia, have been traditionally used as natural remedy in folk medicine by the locals. The current study reports the outcome of antioxidant and cytotoxic investigation of L. indica leaves. To the best of our knowledge, this is the first report of L. indica leaf crude ethanol and its fractionated extracts (hexane, ethyl acetate and water) for evaluation of total phenolic content, antioxidant effect and cytotoxic activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
4
44
1
Order By: Relevance
“…The polar methanolic extract had the highest phenolic concentration, compared to ethyl acetate extract and n-hexane extract. This result different with the previous study reported from Malaysia where the phenolic concentration of 19.15 mg GAE/g from the ethanolic extract, 15.61 mg GAE/g from ethyl acetate and 1.29 mg GAE/g from n-hexane extract (Reddy et al, 2012). Another study conducted in Bangladesh also reported differently (Rahman et al, 2012), indicating that there is a different in phenolic concentration in L. indica leaf.…”
Section: Concentration Of Total Phenolic and Flavonoidcontrasting
confidence: 89%
See 1 more Smart Citation
“…The polar methanolic extract had the highest phenolic concentration, compared to ethyl acetate extract and n-hexane extract. This result different with the previous study reported from Malaysia where the phenolic concentration of 19.15 mg GAE/g from the ethanolic extract, 15.61 mg GAE/g from ethyl acetate and 1.29 mg GAE/g from n-hexane extract (Reddy et al, 2012). Another study conducted in Bangladesh also reported differently (Rahman et al, 2012), indicating that there is a different in phenolic concentration in L. indica leaf.…”
Section: Concentration Of Total Phenolic and Flavonoidcontrasting
confidence: 89%
“…Leea indica, commonly known as Girang in Indonesia, is a plant which can be found in tropical as well as subtropical countries such as Indonesia, Malaysia, Thailand, and other Asian Countries. It is traditionally used by local residents in Indonesia as a natural remedy including malaria possibly due to its phenolic content which has potency as an antioxidant (Reddy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Leea indica: Malaysian rainforests store a large number of plant species which are important as the source of traditional medicine [15]. Leea indica (Vitaceae), commonly known as "Huo Tong Shu" in Malaysia, have been traditionally used as natural remedy in folk medicine by the locals.…”
Section: Introductionmentioning
confidence: 99%
“…The strong antioxidant activities detected in methanol extract in stem and leaves of L. indica could be due to the presence of typical phenolic compounds such as flavonoids and phenolic acids [24]. Such activity of phenolic compounds was mainly due to its redox properties that allow them to act as reducing agent, hydrogen donating agent and singlet oxygen quenching [8,25] . Figure 4 shows the dot blot assay results using DCM and methanol extract of L. indica leaves and stem antioxidant compounds.…”
Section: Semi-quantitative Analysis Of Antioxidant Activity: Dpph Stamentioning
confidence: 99%
“…Methanol extracts from the whole plant of L.indica from Perak Malaysia showed high antioxidant and nitric acid inhibitory activities, whereby its root extract exhibited potential phosphodiestrase inhibitory activities that might be responsible for the strong antioxidant activity in L.indica extracts root [3]. The polar extract of L.indica leaves from Negeri Sembilan Malaysia was reported to exhibit a strong free radical scavenging activity which was due to high content of phenolic compounds [8].…”
Section: Introductionmentioning
confidence: 99%